MOTILITAS DAN VIABILITAS SPERMATOZOA MENCIT (MUS MUSCULUS L.) SETELAH PEMBERIAN EKSTRAK TEMU PUTIH (CURCUMA ZEDOARIA (BERG.) ROSCOE.) - Ashfahani, Elfira Dzikri; Wiratmini, Ngurah Intan; Sukm aningsih, A.A.S.A (2010)
Keywords: temu putih (Curcuma zedoaria (Berg.) Roscoe.); mice (Mus musculus L.); viability; mortility; spermatozoa

(untitled) (Jurnal Biologi Udayana, 2010)
This research was aimed to study the effect of temu putih (Curcuma zedoaria (Berg.) Roscoe.) extract treatment on viability and motility of mice (Mus musculus L.) spermatozoa. The extract was given orally once a day in 35 days. The animals were divided into four groups; one control group and three treatment groups with six replicates. (M0 = control group; M1 = group was given 100 mg/Kg body weight/day; M2 = group was given 200 mg/Kg body weight/day; M3 = group was given 300 mg/Kg body weight/day). The result of the study showed that motility and viability of spermatozoa were decreased significantly (p< 0.05) after receiving temu putih (C. zedoaria (Berg.) Roscoe.) extract for 35 days.